Energy performance sensitivity of a net-zero energy home to design and use specifications*. Issue 1 (2nd January 2016) - Kneifel, Joshua; Healy, William; Filliben, James; Boyd, Matthew
Abstract : The purpose of this report is to test the sensitivity of the energy performance of the National Institute of Standards and Technology (NIST)'s Net Zero Energy Residential Test Facility (NZERTF) design to variation in the assumed specifications of occupant behaviour and building design characteristics using whole building energy simulations. The analysis includes a total of 128 EnergyPlus ( E+ ) simulations (DOE2013 ) considering two levels for each of the seven factors that could impact the energy performance of the NZERTF: building design, air leakage, occupant behaviour, weather, building orientation, and heating and cooling setpoint temperatures. The results for each combination of the seven factors are analysed to determine the magnitude and significance of changing these factors, and the interaction effects between the factors. There is particular focus on the building design results to determine if the energy performance of the NZERTF is more or less stable than that of typical residential construction in Maryland.